Epithelial expression and release of FGF-2 from heparan sulphate binding sites in bronchial tissue in asthma. Issue 7 (28th June 2004) - Shute, J K; Solic, N; Shimizu, J; McConnell, W; Redington, A E; Howarth, P H
Abstract : Background: The most characteristic structural change evident in endobronchial biopsies in asthma, even in mild disease, is subepithelial collagen deposition within the lamina reticularis. This has been associated with progressive loss of lung function and the persistence of airway hyperresponsiveness, and has been linked to airway fibroblast proliferation. A potent fibroproliferative factor in bronchoalveolar lavage fluid in asthma is fibroblast growth factor-2 (FGF-2). FGF-2 is a member of a family of heparin binding growth factors that bind to heparan sulphate proteoglycans (HSPG), an important determinant of FGF-2 activity. This study compared the level of expression and distribution of FGF-2 in relation to HSPG in bronchial tissue from normal and asthmatic subjects. Methods: The distribution of FGF-2 and HSPG in intact and cleaved forms in endobronchial biopsies from normal and asthmatic subjects was examined using an immunohistochemical approach. A novel ELISA based method was developed to detect solubilisation of FGF-2 following addition of heparin and heparitinase to bronchial tissue slices. Results: Immunohistochemical analysis showed that FGF-2 was co-localised to HSPG in epithelial and endothelial basement membranes. Epithelial FGF-2, but not HSPG, was significantly more abundant in patients with mild asthma than in normal subjects. In vitro experiments indicated that FGF-2 was released from binding sites in the tissue by heparin and heparitinase I. Conclusions: FGF-2 is bound by HSPG in bronchial tissue. The mast cell, through the release of heparin and endoglycosidase, may make a unique contribution to tissue remodelling in allergic asthma.